Critical evaluation of an activation program of Sunsilk conditioner by Unilever : a case study of Bangladesh market. - Islam, Tazul (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.